Pengaruh Profitabilitas, Likuiditas, dan Solvabilitas Terhadap Nilai Perusahaan Pada Perusahaan Sektor Teknologi yang Terdaftar di BEI Periode 2021-2022 - Rakhmat Taufiq Hidayat; Ika Neni Kristanti (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2024)
The goal of this study is to examine how profitability, liquidity, and solvency affect the value of technology businesses that are listed on the Indonesia Stock Exchange in the 2021–2022 timeframe. This research is quantitative research using secondary data. The population in this research is all financial data of technology companies listed on the Indonesia Stock Exchange in the 2021-2022 period, totaling 21 companies. The sample selection used purposive sampling so that 88 samples were obtained, namely 11 companies with a quarter period of two years. The analytical tools used are descriptive analysis methods, quantitative analysis, including classical assumption tests, hypothesis tests, coefficient of determination (R2), and regression analysis. The research results explain that profitability has a significant negative effect on company value, liquidity and solvency have no effect on company value